Sociological studies of children and youth. - Kinney, David A., 1960-; Rosier, Katherine Brown (Elsevier JAI, 2005)
This volume of "Sociological Studies of Children and Youth" showcases timely and important work of active, early-career sociologists helping to define the direction of the sub-field. Their work shares basic premises and concerns: children and youth are active agents in their own 'socialization', produce meaning and action collaboratively with peers, and struggle for agency in various social contexts. These themes shape essentially all of the contributions. The volume is organized in two parts. Following the Introduction, six chapters make up Part One, 'Empirical Studies'. Two quantitative analyses lead off: first an examination of residential mobility, peer networks and life-course transitions; second, a look at adolescents' participation in a particular social movement. Two ethnographic studies follow - here the foci are 'Zero Tolerance' school discipline policies, and female athletes' construction of femininity. A comparative content analysis of teen magazine advice columns, and a qualitative study of construction of 'adoptive family' identities, round out Part One. Three chapters constitute Part Two, 'Innovations in Theory and Research Methods'. The first offers an analysis of two films that explore childrens' struggle for agency and control. The next chapter develops a typology of children's participation in social movements, employing fascinating first-person narrative accounts. The final chapter demonstrates the unique ability of group interviews to capture processes through which adolescents accomplish group talk, develop shared perspectives, and construct gender identities.